2022
DOI: 10.3390/su14084616
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Parental External Labour Migration on the Social Sustainability of the Next Generation in Developing Countries

Abstract: Migration is a frequent phenomenon in the current European context. It is culturally differentiated according to every country, and it has a major role in the social sustainability of families and the next generation. This paper aimed to determine the impact of parents leaving to work abroad on the lives of their left-at-home children. This gives rise to a new phenomenon of “social orphans”. This research was carried out with the participation of eight adults who, during their childhood, had a parent who went … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Child abandonment is often related, in scientific literature, with child neglect, child abuse or parental rejection [ 4 ].…”
Section: Child Abandonment Concept and Its Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Child abandonment is often related, in scientific literature, with child neglect, child abuse or parental rejection [ 4 ].…”
Section: Child Abandonment Concept and Its Consequencesmentioning
confidence: 99%
“… Boxplots for (1) comparing the distribution of Shame and Guilt scores of high and low rejection, (2) comparing the distribution of Shame and Guilt scores of low and high abuse, (3) comparing the distributions of the Shame and Guilt scores of the two groups of respondents. The boxplots present [ 1 ] the Lower Whisker (Q1–1.5 IR), [ 2 ] Lower Quartile or Q1, [ 3 ] Median (Q2), [ 4 ] Upper Quartile or Q3, [ 5 ] Upper Whisker Q3 + 1.5 IR. IR represents the Interquartile Range (Q3–Q1).…”
Section: Figurementioning
confidence: 99%
“…Last but not least, family climate also plays a major role in the emotional comfort of adolescents [ 21 ]. In the East European area, this climate has been increasingly affected in the last decade by the migration of one or both parents for lucrative activities in other countries [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Migrant parents are often seen as neglectful of their left-behind children (LBC), who are often termed 'social orphans' or in the case of parents migrating to mostly Western Europe, 'EU orphans' or 'Euro-orphans' (Iosim et al, 2022). Media have highlighted possible extreme negative cases of parental migration (suicide of children, serious crimes etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Researchers also largely agree that the effects on LBC's mental health are often negative, with children presenting vulnerability regarding mental health problems such as anxiety or depression (Fellmeth et al, 2018;Toms ¸a & Jenaro, 2015), health issues (Botezat & Pfeiffer, 2020), risk-taking behaviour such as abusing drugs or alcohol or breaking the law, and increased exposure to violence or bullying (Baudeau et al, 2021). In the literature, LBC are categorised as vulnerable children who are temporarily separated from the care and protection of at least one parent and at risk of significant emotional costs that affect them for shorter (Botezat & Pfeiffer, 2020) or longer (Iosim et al, 2022) periods. In their literature review, Antia et al (2020) found that researchers in the Americas and South Asia have registered only negative changes, but in Eastern Europe, studies found health and well-being indicators for LBC in Georgia and Moldova that did not significantly differ or were even better compared to children of non-migrant parents (Cebotari et al, 2018).…”
Section: Introductionmentioning
confidence: 99%